A Place to connect - Ndungu, Shirlyn (School of Architecture, Planning and Geomatics, 2023)
This dissertation contributes to the discourse on the design of public space in the city. It illustrates a design approach that favours the social welfare of marginalised communities living in Cape Town in particular foreign nationals. By providing a socio- economic anchor for this marginalised community this project aims to assist with their integration into their host nations. The inquiry stems from my lived experience as a Third Culture Kid and student of architecture engaging with the subject of identity and a sense of place. Using lessons learnt from exploring the transition & reentry model of TCKs the proposal suggests ways of assisting foreign nationals in integrating into the city. The document is organised in 4 parts that reflect how ideas of identity formation can be translated into place making strategies. Key themes emerging from this proposal are hybridity, memory, liminality and transparency. I begin by portraying how the concept of hybridity can be understood through the lived experiences of TCKs. I then explore the relationship between memory and place attachment through the lens of a TCK. Ways of translating memory and hybridity are further explored in the precedent studies of The Harpa Concert Hall and Conference Centre and The National Museum of African American History and Culture. The architectural program and design response were reached through the analysis of immigrant settlement and integration requirements. Through mapping the city with parameters set by this study a site is selected in former District 6. The design proposal looks to suggest potential way of supporting the integration of foreign nationals whilst reviving the memory of the once culturally diverse community of District 6. The concept looks to provide spaces for cultural education and enterprise as a way of stimulating public engagement between foreign nationals and local citizens.